2016
DOI: 10.1097/sla.0000000000001367
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Patients Discharged to Skilled Nursing Facilities After Acute Care Hospitalizations

Abstract: Objectives To evaluate previously independent older patients discharged to skilled nursing facilities (SNFs) and identify risk factors for failure to return home and death and development of a predictive tool to determine likelihood of adverse outcome. Background Little is known about the likelihood of return to home, and higher than expected mortality rates in SNFs have recently been described, which may represent an opportunity for quality improvement. Methods Retrospective cohort of older hospitalized p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 15 publications
(11 reference statements)
4
76
0
Order By: Relevance
“…The notable difference in mortality among readmitted patients is consistent with previous work demonstrating, for example, a 5-fold increase in mortality among readmitted patients who underwent AAA repair. 19,32 Although readmitted patients as well as patients who die within 60 days of a procedure have preexisting morbidity that predisposes to poorer outcomes, our study shows that many of the factors related to readmission and mortality are potentially modifiable complications of the surgical procedure.…”
Section: Discussionmentioning
confidence: 81%
“…The notable difference in mortality among readmitted patients is consistent with previous work demonstrating, for example, a 5-fold increase in mortality among readmitted patients who underwent AAA repair. 19,32 Although readmitted patients as well as patients who die within 60 days of a procedure have preexisting morbidity that predisposes to poorer outcomes, our study shows that many of the factors related to readmission and mortality are potentially modifiable complications of the surgical procedure.…”
Section: Discussionmentioning
confidence: 81%
“…5 For older patients, acute health care crises such as a major operation can have a substantial impact on functional capacity, often involving a prolonged recovery extending beyond the acute care hospitalization. 27 Given the high costs associated with SNFs, there has been increased interest in defining the overall utilization of SNFs after discharge. Chen et al 28 reported that SNF utilization among Medicare beneficiaries after coronary artery bypass grafting ranged 16%-19%, and SNF use was as great as 40%-46% among patients being discharged after total hip replacement.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show the importance of transitional care in the process of rehabilitation, rehabilitation, intervention, promotion and even cure of the elderly during discharge to the destination of origin (5,18) , implying significantly the lower re -hospitalizations of these individuals (12,15,19) .…”
Section: A22mentioning
confidence: 99%